Effect of tailored, intensive prehabilitation for risky lifestyles before ventral hernia repair on postoperative outcomes, health, and costs – study protocol for a randomised controlled trial (STRONG-Hernia) - Sofie Anne-Marie Skovbo Jensen; Susanne Vahr Lauridsen; Siv Fonnes; Jacob Rosenberg; Hanne Tønnesen (PLoS ONE, 2025)
Background A substantial untapped potential for risk reduction may be fulfilled by applying intensive lifestyle interventions targeting the co-existing risky lifestyle factors Smoking, Nutrition (both malnutrition and obesity), risky Alcohol intake, and Physical inactivity (SNAP) before surgery. This trial will compare the effect of combined and individually tailored prehabilitation with standard care on postoperative outcomes, health, and cost-effectiveness in short and long term in participants undergoing ventral hernia repair. An interview study will be nested within the randomised trial. Methods The study is a multicenter, parallel-group, superiority randomised clinical trial. A total of 400 adult participants undergoing ventral hernia repair with ≥1 SNAP factor will be allocated to the individually tailored STRONG programme or standard care. The STRONG programme is initiated at least four weeks prior to surgery and consists of six sessions. It is delivered as one session a week, approximately, and includes patient education, motivational, and pharmaceutical supports. The primary outcome is postoperative complications requiring treatment within 30 days. Secondary outcomes address other surgical outcomes, changes in lifestyle, health, and cost-effectiveness. Follow-up takes place after 6 weeks (the end of intervention), at surgery, and 30 days, 90 days, and 6 months after surgery, respectively. Long-term data on health and costs will be obtained from nationwide registries after two years. Eligible trial participants will be invited to a semi-structured interview study at baseline. Their reflections on the STRONG programme and the choice of participating in the trial or not will be explored. Discussion Many patients have multiple SNAP factors adding to the risk of complications related to surgery. As these are modifiable, prehabilitation may be an area with great potential for risk reduction. Nevertheless, no well-acknowledged and evidence-based strategies exist in the preoperative period. The STRONG programme is tailored specifically to the individual patient’s preidentified needs including up to all five common risky SNAP factors and may tap into the large unused potential for risk reduction. Overall, the study will add important new knowledge on the effect of individually tailored prehabilitation on complications and other important outcomes in elective surgery, and also clarify if this intervention will have long-lasting implications. Trial registration www.clinicaltrials.gov (NCT06611462).